Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Laptop Merek ASUS - Anisa Tri Rahayu; Rayhan Gunaningrat; R. Taufik Nur Muftiyanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The aim of this research is to ascertain and assess the ways in which Asus laptop purchase decisions are influenced by brand image, product quality, and pricing. Through the use of the Google Form platform, questionnaires were sent in order to gather data. In the analytical method, multiple linear regression was used in addition to evaluating traditional assumptions. Additionally, IBM SPSS 25 software was used to evaluate the hypotheses both partially (t-test) and concurrently (f-test). The findings demonstrated that while price had no discernible effect on decisions to buy, brand perception and product quality did positively and significantly influence decisions to buy. These findings suggest that while price has little bearing on customer choice, brand perception and product quality are important factors when it comes to Asus laptop purchases.